MENINGKATKAN KETERLIBATAN MAHASISWA DALAM PEMBELAJARAN MELALUI PLATFORM MENTIMETER - Warsihna, Jaka; Ramdani, Zulmi; Amri, Andi (Pusat Data dan Teknologi Informasi Kementerian Pendidikan Kebudayaan, Riset dan Teknologi, 2023)
The presence of various technologies in education can create a condition in which learning process can take place more effectively and meaningfully. The use of various online learning platforms in class is often a strategy for educators to increase students’ interaction and engagement during the learning. In fact, there are still many educators who don't know how to start and utilize the platform in learning. This study aims to redefine best practices that can be used by educators when using Mentimeter platform in learning. The descriptive method is used in this study by involving 40 students who attended lecture activities with Mentimeter platform. The result shows that Mentimeter platform can be used to increase students’ engagement and interaction in the learning process. This can be seen from the number of responses given by the respondents compared to conventional learning activities that do not involve technology in the process. In addition, Mentimeter platform can be a tool for conducting simple formative assessments for educators. Future studies need to present an experimental activity that tests the existence of this Mentimeter platform in learning further.